EKSPLORASI TUMBUHAN OBAT DI HUTAN LINDUNG LUMBAN JULU KECAMATAN LUMBAN JULU KABUPATEN TOBA SAMOSIR - Alexander Manurung; Yunus Afifuddin; Lamek Marpaung (Peronema Forestry Science Journal, 2016)
Lumban Julu protected forest had a huge potential in supply of raw material of medicinal plants. The research was conducted to explore the medicinal plants in the forest. This research aimed to identified species of medicinal plants, analyzed diversity of medicinal plants and analyzed secondary metabolites of medicinal plants. This exploration research of medicinal plants had three stages method. First stage was local knowledge aspect with survey local knowledge. Second stage was biodiversity aspect of medicinal plants with analysis of vegetation data collection. Third stage was phytochemical aspect with detected contain of secondary metabolites. Medicinal plants were obtained as many as eight species with the highest importance value index was Paet-paet (Tithonia diversifolia) at 39.46 and the lowest importance value index was Ciplukan Mini (Physalis minima) at 10.92. Value Shannon-Wiener index of general diversity  (H`) at 1.83, this is showed that the diversity of medicinal plant species in Lumban Julu protected forest was medium. Secondary metabolites test showed Ciplukan Mini (Physalis minima) had complex secondary metabolites. Keyword: Exploration, medicinal plants, secondary metabolite